Monetary policy and Bitcoin - Sören Karau (Deutsche Bundesbank, 2021)
Bitcoin was conceptualized in response to perceived shortcomings in the monetary and financialsystem, not only related to large financial institutions but also to discretionary decision makingin monetary policy. Using high-frequency data and a weekly proxy VAR model, I study theimpact of monetary policy on Bitcoin. The paper shows that monetary shocks have sizableeffects on Bitcoin prices, but that these differ in sign: a disinflationary monetary tightening bythe ECB lowers valuations - consistent with the notion of Bitcoin as a digital gold -, whereasa Fed tightening increases Bitcoin prices. I document similar differences with respect to cen-tral bank information shocks and explore potential explanations by studying various aspects ofthe Bitcoin ecosystem. Exploiting both differences in Bitcoin valuations across currencies andblockchain transaction data, the paper shows that the increased demand for Bitcoin following aUS monetary tightening is primarily driven by emerging markets. I argue that this likely reflectsthe technological and institutional particularities of Bitcoin that make it sought after as globaldigital cashwhen international economic and financial conditions deteriorate.
Keywords: E42; G32; L14; O16; 330; Bitcoin; Blockchain; Monetary policy; Proxy VAR